دور التحول الرقمي للنظام المحاسبي في تفعيل نظام الرقابة الداخلية دراسة ميدانية بمؤسسة سونلغاز الأغواط - حشاني رضوان جلال الدين; زبدة حاج السلامي; رينوبة الأخضر (جامعة عمار ثليجي الاغواط, 2022)
This study was conducted in order to answer the main problem: To what extent can the digital transformation of the accounting system contribute to activating the internal control system? This is because the use of digital transformation or what is known as information technology has become in many fields, and this is due to the speed and accuracy of performance it has achieved, especially with the development and complexity of various administrative and operational processes and the difficulty of monitoring them. To achieve this goal, the study, in its theoretical and practical aspects, contains an introduction, two chapters, and a conclusion. In the theoretical side, we relied on the descriptive analytical approach to show the impact of the independent variable - the internal control system - on the dependent variable - the digital transformation of the accounting system - as well as using the questionnaire method in the practical side of data collection, through which we targeted a group of academics and specialists in the field of competence, and were treated according to the statistical program (SPSS22). The study summarized a set of results, the most important of which are: The digital transformation has a key role in increasing the effectiveness of the internal control system, and improving its procedures and methods.